A Survey of Clinicians’ Preferences Regarding Style and Content of Abdominal Computed Tomography Radiology Reports - Teeravut Tubtawee; Rawiporn Roma; Wiwatana Tanomkiat; Keerati Hongsakul (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE Radiology reports should be readable and understandable, while ensuring there is sufficient pertinent information. This study was conducted to survey the preferred style and content of radiology reports of referring clini-cians.METHODS One hundred and forty questionnaires were sent to clinicians working in departments that frequently request abdominal CT examinations in Songklanagarind Hospital. The participants were asked to rank a set of four radiology reports each with different styles and content (report types A, B, C and D). They were also asked about valued features which should be included in a radiology report. Data were analyzed by normal rank score for the most pre-ferred and using the Kemeny-Young method for preference order. Statistical significance was determined by Kruskal Wallis rank sum tests. P < 0.05 were considered statistically significant.RESULTS Eighty-nine responses were received. The most significant preference was for a structured style with more detail (report type C) (69.7%). Clinical information, quality of examination, measurement of the normal organs and recommendations were statistically significant factors considered appropriate to be included in the radiology report (p < 0.05). Route of administration, dose and name of contrast media were considered statistically inappropriate with statistically significant (p < 0.05).CONCLUSIONS The preferred report style was structured and included more detail and included clinical information, quality of the examination, measure-ments of normal organ and recommendations.